Lower pre-conditioning absolute lymphocyte counts are associated with worse outcomes in haploidentical stem cell transplantation with myeloablative regimen in children - Cui, Kai; Zhang, Senlin; Du, Yueke; Chai, Yutan; Liang, Mingchu; Hu, Shaoyan; Li, Jie (Frontiers in Immunology, 2025)
BackgroundAnti-thymocyte globulin (ATG) is frequently administered for preventing graft-versus-host disease (GVHD) in allogeneic hematopoietic stem cell transplantation (allo-HSCT). In patients with low absolute lymphocyte count (ALC) before conditioning, weight-based dosing of ATG may cause overexposure, negatively impacting prognosis.MethodClinical data of patients with hematological malignancies undergoing haploidentical HSCT (haplo-HSCT) at the Children’s Hospital of Soochow University from January 2020 to June 2023 were collected. This study primarily aims to investigate the association between pre-conditioning ALC and clinical outcomes in pediatric acute leukemia or myelodysplastic syndromes patients receiving myeloablative haplo-HSCT.ResultsWe included 130 patients treated at the Children’s Hospital of Soochow University from January 2020 to June 2023. According to the cutoff of 500/μl, patients were divided into high and low ALC groups. Patients in the high ALC group experienced a higher incidence of II-IV acute GVHD (30.2% versus 13.6%, P = 0.034), 3-year overall survival (OS) and relapse-free survival (RFS) rates (OS: 88.5% ± 3.7% versus 66.9% ± 7.9%, P = 0.013; RFS: 81.4% ± 4.1% versus 56.5% ± 8.1%, P < 0.001), and lower cumulative incidence of relapse (11.3% versus 27.4%, P = 0.013). Pre-conditioning ALC < 500/μl independently predicted worse OS, RFS, and higher relapse risk in multivariate analysis. However, there was no significant difference in immune reconstitution between the two groups.ConclusionPre-conditioning ALC was a significant prognostic factor in pediatric patients undergoing myeloablative haplo-HSCT. Further research is needed to explore whether pre-conditioning ALC can serve as a reference for adjusting ATG dosing.